2009
DOI: 10.1200/jco.2008.16.9599
|View full text |Cite|
|
Sign up to set email alerts
|

Use of 5-α-Reductase Inhibitors for Prostate Cancer Chemoprevention: American Society of Clinical Oncology/American Urological Association 2008 Clinical Practice Guideline

Abstract: A B S T R A C T PurposeTo develop an evidence-based guideline on the use of 5-␣-reductase inhibitors (5-ARIs) for prostate cancer chemoprevention. MethodsThe American Society of Clinical Oncology (ASCO) Health Services Committee (HSC), ASCO Cancer Prevention Committee, and the American Urological Association Practice Guidelines Committee jointly convened a Panel of experts, who used the results from a systematic review of the literature to develop evidence-based recommendations on the use of 5-ARIs for prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 51 publications
0
41
0
2
Order By: Relevance
“…Due to our relatively small sample size we were not able to assess the impact of most prevalent tumor patterns on patient survival. There is a growing concern that use of finasteride can increase the number of patients diagnosed with high-grade tumor (Gleason score > 8) (Kramer et al, 2009, Theoret et al, 2011, Thompson et al, 2013. Food and Drug Administration (FDA) issued a change in safety information of the medication, adding the mentioned warning (Thompson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Due to our relatively small sample size we were not able to assess the impact of most prevalent tumor patterns on patient survival. There is a growing concern that use of finasteride can increase the number of patients diagnosed with high-grade tumor (Gleason score > 8) (Kramer et al, 2009, Theoret et al, 2011, Thompson et al, 2013. Food and Drug Administration (FDA) issued a change in safety information of the medication, adding the mentioned warning (Thompson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for those patients who were treated with radical prostatectomy after positive biopsy in PCPT, there was no significant difference between treatment and placebo arms in terms of pathologic stage, nodal involvement, or margin status. 22 Overall, based on results from PCPT, it seems more likely that finasteride increases predictive accuracy of PSA in the detection of prostate cancer and decreases the overall incidence of prostate cancer. Similarly, results from the REDUCE trial seem to support this hypothesis ( Table 1).…”
Section: Which Pharmaceutical Agents Can Be Considered For Chemoprevementioning
confidence: 99%
“…37,38 A recent guideline from the American Society of Clinical Oncology/American Urological Association has encouraged physicians to discuss chemoprevention with men being screened or considering screening for prostate cancer. 39 However, the 5-alpha-reductase inhibitors were associated with an increased risk for high-grade cancers (Gleason scores 7-10). Although post hoc analyses suggested that selection and sampling biases might have spuriously elevated the risk, 40 the guideline acknowledged that these agents still could be inducing aggressive cancers.…”
Section: Implications Of Screening Trialsmentioning
confidence: 99%